Blank canvas. Volume 1, My so-called artist's journey - Higashimura, Akiko (Seven Seas, 2019)
"The award-winning autobiographical manga by Akiko Higashimura, the creator of Princess Jellyfish, about her high school dream to become a comic book creator! High schooler Akiko has big plans to become a popular mangaka before she even graduates, but she needs to get much better at drawing if she ever wants to reach her goal. Looking for an easy fix, she signs up for an art class, thinking all her problems will soon be solved. She's in for a surprise: her new instructor is a bamboo sword-wielding taskmaster who doesn't care about manga one bit. But maybe this unconventional art teacher is just what she needs to realize her dreams!" -- ONIX annotation.